AN APPROACH TO THE RELATIVE ORDER BASED GROWTH PROPERTIES OF DIFFERENTIAL MONOMIALS - Datta, Sanjib Kumar; Biswas, Tanmay; Bhattacharyya, Sarmila (Italian Journal of Pure and Applied Mathematics, 2015)
In this paper an attempt is taken to study the comparative growth properties of composition of entire and meromorphic functions on the basis of relative order and relative lower order of diﬀerential monomials generated by transcendental entire and transcendental meromorphic functions.